Associated entomofauna with the jamaica cultivation (Hibiscus sabdariffa L.) in the municipality of Chiautla de Tapia, Puebla. - Pérez-Torres, Betzabeth Cecilia; Aragón García, Agustín; Bautista Martínez, Néstor; Tapia Rojas, Ana María; López-Olguín, Jesús Francisco (Instituto de Ecología, A.C., 2009)
In Chiautla de Tapia, Puebla, samplings were carried out at two-week intervals in three cultivated lots with jamaica (Hibiscus sabdariffa L.) from June to September in 2007. The collections were made by means of an entomologic aspirator in a manual way and with beating sheets. Stems, knots, inter-knots, leaves (front and back) and flowers were revised to make an entomofauna diagnosis. A total of 1,856 specimens were collected, of which, were determined 17 species, comprised in 6 orders, 11 families and 19 genera; while 5 morphospecies were not determined. The insects plague that were found causing serious damages to the crop were: Atta mexicana, Sphenarium purpurascens, Melanoplus spp. and Aphis gossypii, and amongst the beneficial insects are San Miguel’s fly, Allograpta sp. (pollinator), Hippodamia convergens and Polister apachus (depredatory species).